PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ACCELERATED INSTRUCTION (TAI) YANG BERORIENTASI TEORI APOS PADA MATERI FUNGSI KUADRAT DI KELAS X-MIA MAN 2 BANDA ACEH - Lasmi Lasmi (Center for Research and Publication UIN Ar-Raniry and Department of Mathematics Education UIN Ar-Raniry., 2017)
Square function is one of mathematical concepts that must be well-comprehended by students. However, there are many students who are having obstacles in understanding the concecpt. For this reason, there is crucial a need of applying a teaching model which make students active in order to construct their knowledge and comprehension of the concept. The purpose of this study was to examine students’ achievements, detect the students’ activities, examine the students’ responds to the applying TAI model oriented by APOS theory. The classroom action research (CAR) was used in this study with 28 students of grade-10 (classroom X-MIA.1) of MAN 2 Banda Aceh in academic year 2015/2016 as the subjects of this study. The instruments used in this study were the student observation form, teacher observation form, student respond questionnaire toward the application of the learning model and the test items. The data was analyse by using percentage of the descriptive analysis. The results showed that in cycle I to IV: (1) 89,29% students achieved the minimum level of students’ achievement; (2) students were moderately active; (3) 100% students enjoyed the learning model and were agreed if in the next teaching and learning to be used the similar model. Consequently, the model of TAI oriented by APOS theory is an appropriate model used in the teaching and learning of square function concept.